Principles of heating ventilating and air conditioning : a textbook with design data based on the 2017 ashrae handbook of fundamentals - Howell, Ronald H. 1935- (ASHRAE, 2017)
"A textbook with design data based on the 2017 ASHRAE Handbook of Fundamentals"-- Provided by publisher
Keywords: Heating -- Textbooks.; Ventilation -- Textbooks.; Air conditioning -- Textbooks.; elektronické knihy; electronic books